1993
DOI: 10.3382/ps.0720172
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Multiple Blood Sampling Regimens Using an Indwelling Vascular Access Device for Investigations of the Hen's Ovulatory Cycle and Calcium Metabolism ,

Abstract: The objectives of the present study were to compare the effects of two regimens of serial blood sampling on the concentrations of hormones and ions during the ovulatory cycle of the domestic hen, and to examine the effectiveness of an indwelling vascular access device for repeated collection of blood samples. Single Comb White Leghorn hens were bled every 2 h over a period of 24 to 26 h, either from one oviposition to the next oviposition (OVIP-OVIP), or from 10 h prior to ovulation until the same time 24 h la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Plasma concentration of E2, P4 (Ruschkowski, 1993;Etches, 1996 andAhmed Nagwa, 1998) and ionic calcium (Singh et al, 1986;Frost et al, 1991 andRuschkowski, 1993) varied according to the stage of egg formation. Maximum peaks of E2, P4 and ionic calcium were determined immediately post-oviposition.…”
Section: Hormones and Calcium Level At Successive Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma concentration of E2, P4 (Ruschkowski, 1993;Etches, 1996 andAhmed Nagwa, 1998) and ionic calcium (Singh et al, 1986;Frost et al, 1991 andRuschkowski, 1993) varied according to the stage of egg formation. Maximum peaks of E2, P4 and ionic calcium were determined immediately post-oviposition.…”
Section: Hormones and Calcium Level At Successive Productionmentioning
confidence: 99%
“…Maximum peaks of E2, P4 and ionic calcium were determined immediately post-oviposition. Ruschkowski (1993) reported that a transitory peak in plasma estradiol 17 concentration immediately following oviposition.…”
Section: Hormones and Calcium Level At Successive Productionmentioning
confidence: 99%